Amphibians And Reptiles - Das, Indraneil; Martin, Veronica; Leah, Veronica; Awang Khairul, Ikhwan; Pine, Anthony K. (UNIMAS Publisher, 2020)
The amphibians and reptiles noted from Sadong Jaya during a rapid biodiversity assessment are listed.